Investor protection within the securities industry / Bhuvaneswari Krishnamurthy - Bhuvaneswari, Krishnamurthy (1997)
Laws are nonnally enacted with reference to social objectives. The rules and regulations that govern the Securities lndustry have been enacted with a view to providing Investor Protection. The objective of this work is to examine the body of laws that affect an individual investor in making his investment decisions. This work is centered around the provisions contained in the Malaysian Companies Act 1965, the Securities Industry Act 1983, and the Securities Commission Act 1993 and their impact on the Kuala Lumpur Stock Exchange. Regulation of the Securities Industry in Malaysia only spans the last three decades and hence reference has been made to the regulatory provisions and case law from other jurisdictions with a longer track record than us. Examples have been drawn from the laws of the United States because it is a forerunner in the field of securities regulation, Australia because it is an important regulator within the region and because our regulators have modelled our own regulations on that of our Australian counterparts, and Singapore because of socio-political similarities that exist between our countries, which is reflected in the similarity of the provisions contained in the laws of both countries. Since all laws relating to the Securities 1ndustry are either directly or indirectly concerned with Investor Protection. this work will restrict itself to the examination of certain key areas. ln Chapter Ill attention is focused on the Kuala Lumpur Stock Exchange and its constituent parts with a view to highlighting the protections afforded to the investor by the market structure. The securities industry prevents direct access to the market by investors who are required to channel their funds through financial intermediaries. 1n Chapter TV this work therefore attempts to uncover whether the intermediaries are acting in the interests of their clientele. Chapter V considers the effect of insider trading on the market with special emphasis on the ways in which it threatens Investor Protection. Finally Chapter VJ examines the effectiveness of the regulatory bodies in safeguarding investor interests with specific reference to the Securities Commission. Based on the foregoing the writer intends to conclude that Investor Protection ought to be the rationale behind all future securities regulation and to this end cirtain recommendations have been made in the concluding chapter.